PENGARUH FAMILY OWNERSHIP TERHADAP KINERJA KEUANGAN: STRATEGI BISNIS DAN AGENCY COST SEBAGAI VARIABEL MODERATING - Anita Anita; Kirmizi Kirmizi; Enni Savitri (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2016)
The purpose of this study is to examine the effect of family ownership on financial performance moderated by business strategy and agency cost. The sample of the stuydy are manufacturing companies listed on Indonesia Stock Exchange period2007-2014, 45 companies, which has family ownership at least 20%. By using a model multiple regression analysis with EView version 9 is used. Result show that family ownership has an effect on financial performance, business strategy and agency cost has moderated on the relationship between family ownership and financial performanceKata kunci : Financial Performance, Family Ownership, Business StrategyAgency Cost